Optimizing nutritional education to improve quality of life in cancer patients - Sukartini, Tintin; Zamroni, Asroful Hulam; Marina, Navy Sealsi Adinda Prisca; Syahri, Alfi; Ismail, Fachril; Tadi, Tadi; Qothrunnadaa, Azka; Tisel, Yulmira Maria; Tabik, Albertina Dete; Dorman, Johanes Eban B.; Damayanti, Elvi Kurnia (Universitas Muhammadiyah Magelang, 2025)
Cancer remains a major contributor to morbidity and mortality globally. The disease itself and its treatments often lead to significant challenges that negatively impact patients' quality of life. The objective of this community service initiative was to enhance the knowledge and understanding of cancer patients regarding their nutritional needs through a focused educational program. The method employed was a health education approach that included demonstrations. The activity involved 30 cancer patients, all over 18 years of age, who were undergoing radiotherapy or chemotherapy. The results showed a significant improvement in the participants' quality of life, specifically in their knowledge and understanding of nutrition. The pre-intervention score of 50% increased to 87.3% post-intervention, representing a 37.3% improvement. This demonstrates that the application of education on nutritional management can effectively improve patients' nutritional status. A good nutritional status is expected to enhance the overall quality of life for cancer patients undergoing medical treatment, as they are better equipped to implement nutritional management strategies in line with their health conditions and medical recommendations.